PENGEMBANGAN E-MODUL BERBASIS CHEMO-EDUTAINMENT PADA MATERI KESETIMBANGAN KIMIA UNTUK MENINGKATKAN LITERASI SAINS PESERTA DIDIK - Romita Erika Narestifuri; Rusly Hidayah (Universitas Negeri Makassar, 2022)
This research aimed to determine the feasibility of E-Module based on Chemo-Edutainment on chemical equilibrium material to improve students' scientific literacy. The method used is 4D (define, design, develope, and disseminate), but the disseminate stage is not carried out. Based on the validity test, it was found that the E-Module had valid and very valid criteria, covering aspects of presentation obtained 90.67%, linguistic aspects 86.67%, graphic aspects 80.00%, and content aspects 88.14%. Based on the student response questionnaires, result of presentation ≥ 80,1% stated that it was easy to use the E-Module, so it had very practical criteria. The N-gain calculation uses the Pre-Test and Post-Test values which are used to determine the increase in students' scientific literacy with an average N-gain result of 86.30% of students being in high criteria. The results of the Wilcoxon obtained the Asymp value. Sig. (2-tailed) 0.000 (H0 is rejected). Thus, the E-Module based on Chemo-Edutainment on chemical equilibrium material is appropriate to be used to improve students' scientific literacy.